Gender identity and perception in virtual spaces: the impact of avatar gender transition on the ZEPETO platform - Kang, Jiyoung; Rhee, Hyunjung (Frontiers in Virtual Reality, 2025)
This study examines how avatar gender transitions in the metaverse influence user identity and gender perception, focusing on the cultural and social implications of these experiences. Conducted on the ZEPETO platform, the research involved female participants adopting male avatars to explore the effects on identity confirmation and self-identification. The study analyzes how metaverse elements, such as avatar representation, embodiment perception, and avatar-space interaction, contribute to identity formation and challenge traditional gender norms. Results indicate that transitioning to male avatars enhances avatar identification and identity confirmation, with these effects extending to users’ real-world gender identities. These findings highlight the metaverse’s potential as a transformative space for exploring and reshaping gender identities, emphasizing the need for further research into the cultural and spatial dynamics of virtual environments.